Are IL-1 family cytokines important in management of sickle cell disease in Sub-Saharan Africa patients? - Siransy, Liliane K.; Dasse, Romuald S.; Adou, Honoré; Kouacou, Patricia; Kouamenan, Sidonie; Sekongo, Yassongui; Yeboah, Richard; Memel, Charlene; Assi-Sahoin, Aniella; Moussa, Salimata Y.; Oura, Doris; Seri, Jocelyne (Frontiers in Immunology, 2023)
Sickle cell disease (SCD) is the most common genetic disease found in Africa and throughout the world. It is responsible for a high rate of hemolysis, systemic inflammation, and modulation of the immune system with the involvement of immunological molecules, such as cytokines. IL-1β is a major inflammatory cytokine. IL-18 and IL-33, members of IL-1 family, also exhibit characteristics of inflammation-related cytokines. Thus, in order to contribute to the evaluation of the severity and prognosis of SCD in Africa, this study aimed to estimate the cytokine response, in particular the levels of cytokines of the IL-1 family, in sickle cell patients living in a Sub-Saharan country. Ninety patients with a diagnosis of SCD were recruited with different hemoglobin types. The assessment of plasma cytokines in SCD patients revealed significantly increased levels of IL-1 family cytokines in crisis compared to steady state, suggesting a substantial involvement of these cytokines in clinical exacerbation. This suggests the possibility of a causal effect in the SCD pathology and can open the way to define better care, pointing toward new therapeutic avenues for sickle disease in Sub-Saharan Africa.